1983
DOI: 10.1111/j.1752-1688.1983.tb05935.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF TREATED BLEACHED KRAFT MILL EFFLUENT ON EGGS AND PROLARVAE OF STRIPED BASS (MORONE SAXATILIS)1

Abstract: Striped bass (Morone saxatilis) eggs and prolarvae were exposed to a range of treated bleached kraft mill effluent (BKME) concentrations from 0 to 20 percent effluent by volume (v/v) under continuous flow test conditions. The treated BKME used in the study before dilution had a BOD5 of 18 to 25 mg/l, TSS of 60 to 185 mg/l and true color of 1750 to 1755 mg/l. No mortality attributable to BKME was found in three separate egg studies. No delayed hatching of the eggs occurred in any of the BKME treatments relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…In contrast, survival in the Wateree River water was less than that in both control waters. Although Burton et al (1983) detected no chlorinated phenols in the Wateree River, their detection limits were 10-fold higher than those in our study.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In contrast, survival in the Wateree River water was less than that in both control waters. Although Burton et al (1983) detected no chlorinated phenols in the Wateree River, their detection limits were 10-fold higher than those in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…Mortality of larval striped bass in water from the Wateree River was previously documented and attributed to the low hardness, alkalinity, and conductivity of the river water (Burton et al 1983). However, striped bass have historically survived and reproduced in the soft fresh water of the Santee, Congaree, and Wateree rivers, although such water quality conditions may not be optimal for their survival.…”
Section: Discussionmentioning
confidence: 96%
“…Increase in the amount of toxic substances in water kills zooplankton and fish, affecting the terrestrial ecosystem (Burton et al 1983). Other problems may occur due to failure of the treatment processes employed to treat the pulp and paper mill effluent.…”
Section: Toxicity Of Recalcitrant Compoundsmentioning
confidence: 99%
“…Additionally, decreased number of juveniles, physiological and skin diseases, and changes in communities, population structure, and in growth rates of fish have been observed (Sepúlveda et al 2002). Furthermore, effluents from pulp bleaching impair the quality of fish and fish flesh in the receiving waters (Herve 1991;Redenbach 1997).Increase in the amount of toxic substances in water kills zooplankton and fish, affecting the terrestrial ecosystem (Burton et al 1983). Other problems may occur due to failure of the treatment processes employed to treat the pulp and paper mill effluent.…”
mentioning
confidence: 99%
“…Vuorinen & Vuorinen (1987) found that hatching of brown trout in 2% bleached kraft mill effluent (BKME) was lower, and that sac fry were shorter than the control group and died within three weeks after hatching. Burton et al (1983) did not observe any changed mortality or delayed hatching of stripped bas egg exposed to BKME. Egg from unexposed rainbow trout fertilized and incubated in BKME showed no changes in hatching frequency, and the growth rate of sac fry was higher (Grotell, pers: comm.).…”
Section: Resultsmentioning
confidence: 60%